2019
DOI: 10.1002/psp4.12382
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Potential Drug–Drug Interactions Between Dabigatran Etexilate and a P‐Glycoprotein Inhibitor in Renal Impairment Populations Using Physiologically Based Pharmacokinetic Modeling

Abstract: Plasma concentrations of dabigatran, an active principle of prodrug dabigatran etexilate ( DABE ), are increased by renal impairment ( RI ) or coadministration of a P‐glycoprotein inhibitor. Because the combined effects of drug–drug interactions and RI have not been evaluated by means of clinical studies, the decision of DABE dosing for RI patients receiving P‐glycoprotein inhibitors is empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…A combination of increased absorption and reduced elimination can also lead to increased DOAC exposure that has previously not been investigated. A physiologically based pharmacokinetic model calculated that dabigatran C min will significantly increase in patients with moderate renal impairment who concomitantly take the P-gp inhibitor verapamil [72]. Despite the statement in the product label that only recommends a dose reduction to 110 mg twice daily, the authors suggested that the significantly increased C min values might be preventable by reducing dabigatran doses further to 75 mg twice daily [72].…”
Section: Drug-drug Interactions Affecting Doac Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of increased absorption and reduced elimination can also lead to increased DOAC exposure that has previously not been investigated. A physiologically based pharmacokinetic model calculated that dabigatran C min will significantly increase in patients with moderate renal impairment who concomitantly take the P-gp inhibitor verapamil [72]. Despite the statement in the product label that only recommends a dose reduction to 110 mg twice daily, the authors suggested that the significantly increased C min values might be preventable by reducing dabigatran doses further to 75 mg twice daily [72].…”
Section: Drug-drug Interactions Affecting Doac Therapymentioning
confidence: 99%
“…A physiologically based pharmacokinetic model calculated that dabigatran C min will significantly increase in patients with moderate renal impairment who concomitantly take the P-gp inhibitor verapamil [72]. Despite the statement in the product label that only recommends a dose reduction to 110 mg twice daily, the authors suggested that the significantly increased C min values might be preventable by reducing dabigatran doses further to 75 mg twice daily [72]. However, as long as clinical trials investigating pharmacokinetics and clinical effects of this complex clinical situation are missing, it will be unclear whether patients treated with 110 mg twice daily are at an increased risk of bleeding and what dabigatran efficacy will be if doses are further reduced.…”
Section: Drug-drug Interactions Affecting Doac Therapymentioning
confidence: 99%
“…Particular care should be taken in the CKD setting where the combination of reduced renal clearance and coadministration of P-glycoprotein inhibitors may increase bleeding risk. 137 Factor Xa DOACs also depend on the Pglycoprotein pathway for metabolism, and interactions with inducers and inhibitors have been described. Moreover, factor Xa DOACs are metabolized by cytochrome P450 and drug effectiveness may be affected by coadministration with CYP3A4 inhibitors (e.g., fluconazole, ketoconazole, itraconazole, and vorconazole) or CYP3A4 inducers (e.g., rifampin and phenytoin).…”
Section: Drug/drug Interactionsmentioning
confidence: 99%
“…A few PBPK models for DABE has been published so far. 31,35 Among these, the model developed by Moj et al is comprehensive and can predict DABE, DAB, and DAB-G. However, that model used the salt solubility of DABE (1.8 mg/ml) to develop the absorption model.…”
Section: Discussionmentioning
confidence: 99%
“…A few PBPK models for DABE has been published so far 31,35 . Among these, the model developed by Moj et al is comprehensive and can predict DABE, DAB, and DAB‐G.…”
Section: Discussionmentioning
confidence: 99%